Diagnóstico de la cadena de frío en Colombia (2018)
The incorrect handling of perishable products has affected the health of people, while generating high levels of losses and waste. This situation is more visible in the food sector, because of the impli-cations that these products have on the lives of human beings. The detailed fulfillment of the cold chain is the best way to guarantee the correct conservation of the perishable products, the food safety and the quality of these, at the same time it allows to decrease the loss and waste throughout the different processes from the production until consumption. In Colombia specifically, based on recent studies, a high volume of food has been determined that does not reach human consumption due to losses, caused by deficient processes, and waste, due to poor handling or disposal of these. A deficient compliance of the cold chain, less than 90%, clearly indicates that the processes are not being carried out correctly, sometimes due to ignorance and others due to lack of technical and financial support; overcoming these indicators means improve quality of products, health of people, reducing losses and waste products and promote the economic growth of agricultural producers in the country.